Thick filament molecular interfaces play a critical role in the pathogenesis of hypertrophic cardiomyopathy - Debabrata Dutta; Yuri Kim; Carolyn Y. Ho; Jonathan G. Seidman; Christine E. Seidman; Roger Craig; Raúl Padrón (Proceedings of the National Academy of Sciences, 2026)
Hypertrophic cardiomyopathy (HCM) variants in genes encoding the myosin heavy chain (MHC) ( MYH7 ), myosin light chains ( MYL2 and MYL3 ), and cardiac myosin binding protein-C (cMyBP-C, MYBPC3 ) lead to cardiac hypertrophy, with abnormal contractility, relaxation, and energy consumption. Here, we defined the structural consequences of pathogenic and benign missense variants in these genes by mapping 233 variants ( MYH7 , n = 175; MYBPC3 , n = 41; MYL2 , n = 12; MYL3 , n = 5) onto a cryo-EM-based atomic model of the human cardiac thick filament. We identified HCM variants residing in 30 molecular interfaces of the complex thick filament interactome, including the two main interfaces of the myosin interacting-heads motif (IHM), and interfaces involving the MHC, essential and regulatory light chains, and cMyBP-C. None of the 21 variants classified as benign were within interfaces. We demonstrated earlier disease onset and adverse outcomes in HCM patients with pathogenic variants within vs. outside of molecular interfaces, emphasizing their importance in normal thick filament function and improving risk stratification of patients.